The Analysis of Erosion Rates in 2020 and 2024 Using Geographic Information Systems in the Liliba River Border Area, Liliba Village, Oebobo District - Glory Mei Sanada Silalahi; Muhammad Husain Hasan; Poppy Haryani (Universitas Negeri Semarang, 2026)
Liliba Subdistrict , Kupang City , is area border rivers in semi-arid regions that experience pressure consequence development settlements and changes use Land . Despite having a long dry season, concentrated rainfall during the rainy season has the potential to increase erosion rates and the risk of land degradation. This study aims to analyze changes in erosion rates and the dynamics of erosion hazard levels influenced by changes in land use in the Liliba River riparian area for the period 2020–2024, as well as to develop land use guidelines that support sustainable environmental management in accordance with the Kupang City Spatial Plan (RTRW). The method used is the Universal Soil Loss Equation (USLE) which includes factors of rainfall erosivity (R), soil erodibility (K), slope length and gradient (LS), land use (CP) which are analyzed spatially using Geographic Information Systems (GIS) to compare conditions in 2020 and 2024. The results of the study show that the average erosion rate increased from 300.45 tons/ha/year in 2020 to 889.09 tons/ha/year in 2024. This change was followed by a shift in the dominance of the erosion hazard level from a heavy class covering an area of 253.75 ha in 2020 to a very heavy class covering an area of 281.32 ha in 2024. Based on the results of the analysis, land use guidelines are prepared according to the level of erosion hazard by emphasizing the implementation of soil and water conservation and protection of riparian areas. This study shows that changes in land use in riparian areas in semi-arid areas contribute to increasing erosion hazards, so integrated land use management is needed to support environmental sustainability in Liliba Village